Autism and English in Iceland: Are young Icelanders with autism spectrum disorders using English differently than their peers? - Karen Kristín Ralston 1969- (2016)
This triangulation study looks at how young Icelanders with autism spectrum disorders are using English in comparison to their non-autistic peers. This is the first study in Iceland to look at this issue and was set up in two parts. In the first part of the study, 5 parents were interviewed about their children with ASD who claimed to prefer speaking English rather than Icelandic. In these interviews, parents were asked questions about their children’s language development, personal interests and how their children use English in their daily lives. The results suggested that new patterns of language development and language usage might be emerging among some young Icelanders with ASD due to English exposure through digital sources and other motivational factors. In the second part of the study, 9 students with autism spectrum disorders in the age bracket of 13-14 years and 6 students with autism spectrum disorders in the age bracket of 16-17 years, were compared to control groups of age equivalent, non-autistic peers. This comparison was made by measuring these students’ receptive lexical vocabulary in English. Also these individuals answered questions in a written survey about where and how often they use English on a weekly basis. The results from the survey revealed only 3 differences in how the students with autism spectrum disorders were using English when compared to their peers. These differences were connected to reading in English and writing in English on YouTube and other social media. The results of the vocabulary tests revealed no significant differences, supporting that young Icelanders with autism spectrum disorders are attaining a level of receptive lexical vocabulary that is similar to their non-autistic, age equivalent peers.